Avaliação da influência da equação de estado na conversão da vazão de gás natural para um estado termodinâmico de referência - Almeida, Rafael de (2023)
Due to regulation and strategic considerations in Brazil, the measurement of liquid or gaseous hydrocarbon flow must be reported to the National Agency of Petroleum, Natural Gas, and Biofuels (ANP) in volumetric terms and under the so-called "ANP standard condition," defined as 0.1 MPa and 20°C. Therefore, any flow measurement processes for these fluids carried out under different thermodynamic conditions must be converted to the volume under the "ANP standard condition." To do so, a thermodynamic equation of state is required, which estimates the properties of the measured fluids under both the measurement and standard conditions, such as density and compressibility factor, among others. Because it is a multicomponent fluid, converting the properties of natural gas depends on complex equations of state, which consider binary and ternary interactions between components and involve uncertainties associated with physical and chemical phenomena. This text evaluates the performance of the GERG-2008 equation of state, considering the thermodynamic states and chemical compositions relevant in natural gas wells located off the Brazilian coast. When converting the flow rates to the "ANP standard condition," differences of up to 0.3% were observed between the estimates from the equation of state and experimental data available in the literature. These differences should be considered in the calculation of the measurement uncertainty under the standard condition.